1A.03: TRANSCRIPTIONAL NETWORK ASSOCIATED WITH THE CONTRACTILE PHENOTYPE OF SMOOTH MUSCLE CELLS IN HUMAN CAROTID ATHEROSCLEROSIS. (June 2015) - Cerutti, C.; Paultre, C.Z.; Gustin, M.P.; Lohez, O.; Feugier, P.; Li, J.Y.; Bricca, G.
Abstract : Objective: During atherogenesis, vascular smooth muscle cells (VSMCs) undergo a phenotypic modulation leading to migration and loss of contractility. Here we propose a gene regulatory network specific of the contractile phenotype of the carotid VSMCs from transcriptomic data. Design and method: Human carotid atheroma plaque (ATH, Stary>4) and nearby macroscopically intact tissue (MIT, Stary<3) of 32 patients were analysed by microarrays (Affymetrix HuGene-1.0ST). Histological analysis ensured the large predominance of VSMCs in MIT. Vascular smooth muscle contraction (VSMcontr) involved 119 genes (KEGG database). Transcriptional regulators (TRs) were obtained from Genomatix© and KEGG. Co-expression of TRs and VSMcontr genes was assessed by significant pairwise correlations (p < 10–3) between expression levels across the 32 patients. For each TR, its connecting index (CI) with VSMcontr was obtained from its connectivity, number of its significant (p < 0.001) correlations with the VSMcontr genes, weighted by its expression centile rank. Results: Forty VSMcontr genes were under-expressed (localFDR< 5%) in ATH vs MIT: 11 genes encoding contractile proteins and their kinases/phosphatases, 11 genes encoding receptors and Ca2+/K+ channels, and 18 genes involved in Ca2+ or G-protein signalling. They were taken as the core-VSMcontr gene set. TRs showing the highest CI with core-VSMcontr in MIT that strongly decreased in ATH were taken as representative of the contractile phenotype of VSMCs. Conversely, TRs whose CI with core-VSMContr strongly increased reaching the highest levels in ATH were taken as representative of the synthetic phenotype of VSMCs in ATH. Ninety-one TRs had high positive (CI+) or negative (CI-) connecting index with core-VSMcontr specifically in MIT or ATH: 49 TRs with high CI+ (including NRF1, SRF and THRA) and 16 with high CI- (including HIF1A and STAT1) were MIT-specific, whereas 17 (including ERCC6, PRRX1 and ARID5B) and 9 (including RNF4 and USF1) other TRs had respectively high CI+ and high CI- and were ATH-specific. Conclusions: The regulatory network around core-VSMcontr genes showed clear changes in ATH compared to MIT by reducing the involvement of TRs related to cell contractility and energy metabolism, and increasing that of TRs related to cell dedifferentiation, proliferation and migration or with yet unknown function.